Recursive Anchoring Techniques in Astronomical Data Analysis - Naik, Vijaya (Journal of Research in Science and Engineering, 2025)
The conventional approach to astronomical research assumes that large - scale observational data is necessary to define cosmic structures. This paper proposes a recursive anchoring method where a fraction of the dataset, when correctly defined within a recursive framework, can reconstruct the same “center of existence” as a full dataset. By leveraging singularities as recursive attractors, we demonstrate that full data observation is redundant and that scientific discovery may be better framed as an act of stabilizing recursion rather than measuring reality. This has significant implications for dark matter, dark energy, and the fundamental limits of observational science.